Biosurfactant Producing Bacteria on Oily Areas of Ruminant Skin: Biosurfactant Producing Bacteria on Oily Areas of Ruminant Skin - Azizollah Ebrahimi; Najmeh Tashi; Saeid Karimi (Iranian Journal of Pharmaceutical Sciences, 2011)
Biosurfactants are surface-active compounds produced by microorganisms. In this study, we collected 60 inguinal area and ear canal samples from cows, sheep, and goats (each, 10 animals) and screened for biosurfactant-producing bacteria. We also determined the genera of culturing strains. Fifty six hemolytic bacterial strains (27, 22 and 7, from cows, sheep and goats, respectively) were isolated. Oil spreading test and bioemulsifying activities were measured for all isolates. The cows’ samples had higher population of positive strains than other animals, so that 5 isolates from inguinal area and 4 from ear canal samples (16.1%) were positive for all tests. For sheep, the numbers were 6 and one (12.5%) while for goats one and two (5.3%), respectively. Totally, 19 isolates (33.9%) were positive for all examinations out of them 12 were gram positives. The microorganisms isolated in this study could well be sources of novel biosurfactants. Further investigation into the composition of the biosurfactants and phylogenetic determination of biosurfactant producing bacteria is suggested.